Effect of Different Types of Malocclusions on Maximum Bite Force in an Iranian Population - Alamdari, Ali; Salehi Vaziri, Abbas; Ahmadvand, Atefe (Galen Medical Journal, 2024)
Background: Limited studies are available on how different malocclusion types and associated factors influence maximum bite force (MBF). Thus, this study aimed to assess the effect of the types of malocclusion, overbite, and overjet on MBF in an Iranian population. Materials and Methods: This cross-sectional, descriptive-analytical study involved 80 participants with no prior orthodontic treatments or jaw surgeries. The type of malocclusion of the participants was determined, and their overjet and overbite were measured. Their MBF was also measured by a strain gauge. The date were analyzed by one-way ANOVA and LSD test (alpha = 0.05). Results: The mean MBF was 386.24 N in the study population (range 197 to 701 N). The mean MBF was 413.38 N, 381.11 N, and 165.33 N in Class I, Class II, and Class III patients, respectively (P<0.05). Class III patients exhibited significantly lower MBF compared to the other groups (P<0.05). Overjet and overbite had significant effects on the MBF (P<0.05). The decreased overjet group showed significantly lower MBF compared to both the normal overjet (P = 0.028) and increased overjet groups (P = 0.011). Similarly, the deep bite (P = 0.041) and edge-to-edge bite groups (P = 0.02) had significantly lower MBF compared to the normal bite group. Conclusion: The results indicated that malocclusion type significantly influenced the MBF of the study participants, with Class III patients demonstrating notably lower MBF compared to other groups.